Assortative Mating on Ideology Could Operate Through Olfactory Cues. Issue 4 (2nd September 2014) - McDermott, Rose; Tingley, Dustin; Hatemi, Peter K.
Abstract : Mates appear to assort on political attitudes more than any other social, behavioral, or physical trait, besides religion. Yet the process by which ideologically similar mates end up together remains ambiguous. Mates do not appear to consciously select one another based on ideology, nor does similarity result from convergence. Recently, several lines of inquiry have converged on the finding that olfactory processes have an important role in both political ideology and mate selection. Here we integrate extant studies of attraction, ideology, and olfaction and explore the possibility that assortation on political attitudes may result, in part, from greater attraction to the scent of those with shared ideology. We conduct a study in which individuals evaluated the body odor of unknown others, observing that individuals are more attracted to their ideological concomitants.